2017
DOI: 10.5897/ajar2017.12605
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivariate probit on determinants of sesame farmers market outlet choices in Gimbi District, Ethiopia

Abstract: Sesame (Sesamum indicum L.) is an important crop produced in Ethiopia for oilseed production and it was ranked first in total production from oil crops in 2013. The study is based on a survey of 166 farmers covering six kebeles in Gimbi district, Ethiopia with the objectives of identifying factors affecting choice of market outlet of sesame producers in the study area. Data were collected from both primary and secondary sources in 2015/2016. Multivariate probit model was for analysis. The results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
3
0
0
Order By: Relevance
“…According to the result, producers may obtain maximum price per their supply to final consumer than other market outlets. This finding concurs with Temesgen et al (2017) stated that the market price of sesame has a positive and significant effects on consumer's market outlet choice whereas a negative and significant effect on collector outlet choice.…”
Section: Market Informationsupporting
confidence: 91%
“…According to the result, producers may obtain maximum price per their supply to final consumer than other market outlets. This finding concurs with Temesgen et al (2017) stated that the market price of sesame has a positive and significant effects on consumer's market outlet choice whereas a negative and significant effect on collector outlet choice.…”
Section: Market Informationsupporting
confidence: 91%
“…Quantity supply: quantity of sesame supply was positively and significantly influence the likelihood of choosing traders and cooperative market outlet at 5% and 10% significance level respectively and negatively influenced the likelihood of choosing consumer and collector outlet at 10% level of significance. Therefore, this result was in line with the finding of Fikiru, et al [20] that if the household head is produced more quantity the probability of choice of cooperative outlet increased relative to wholesaler outlet and Bezabih, et al [21] indicated that large volume of sale motivates households to prioritize the channels and decide to use the best alternative. Those households with large volume of sesame were more likely to sell to private traders and cooperative and less likely to sell to consumers' collector outlet.…”
Section: Determinants Of Sesame Market Outlet Choicesupporting
confidence: 85%
“…Thus, the estimated results suggest that market access could motivate farmers to participate in irrigation farming. This is in line with previous studies (Fikirie, 2017;Nonvide et al, 2018), which found a significant positive relationship between market channels and irrigation participation.…”
Section: Determinants Of Participation In Irrigation Farmingsupporting
confidence: 93%